Electrical stimulation and isokinetic training: effects on strength and neuromuscular properties of healthy young adults - Avila,MA (2008)
OBJECTIVE: To assess the effects of neuromuscular electrical stimulation (NMES) associated with an isokinetic training program in healthy young men and women. METHODS: Twenty participants (ten men, ten women; 21±1.5 years) underwent an isokinetic training program for knee extensors of both sides (three sets of ten concentric repetitions at 30°/s) twice a week for four weeks. One limb underwent only the isokinetic strength training (Ex) while the other underwent the same training but with NMES associated with each contraction (Ex+NMES). The current used for NMES was the Russian current (frequency of 2,500Hz, 50 bursts/s and pulse duration of 200µs). Isometric and isokinetic concentric extensor torque at 30°/s were evaluated. RESULTS: The groups increased their peak torque in both test procedures, with no difference between Ex and Ex+NMES. The angle of peak torque increased for the Ex limb, thus showing a change in the tension-length relationship of the muscle group tested, which did not occur for the Ex+NMES limb. There was also a decrease in acceleration time in both limbs, without any effects from NMES on this variable. CONCLUSIONS: These results showed that the association between NMES and isokinetic concentric voluntary strength training did not improve the strength gains and neuromuscular properties of voluntary strength training itself for healthy young participants of both genders.